2004
DOI: 10.1086/380505
|View full text |Cite
|
Sign up to set email alerts
|

The Luminous X‐Ray Source Population in M51 Observed withChandra

Abstract: We present the results of two Chandra observations (separated by 1 yr) of the population of X-ray sources in the spiral galaxy M51 (NGC 5194 and NGC 5195). One hundred and thirteen X-ray sources have been detected in an 8A4 Â 8A4 (20:4 Â 20:4 kpc) region, and 84 and 12 of them project within the disks of NGC 5194 and NGC 5195, respectively. Nine and 28 sources have luminosities exceeding 1 Â 10 39 ergs s À1 (ultraluminous X-ray sources or ULXs) and 1 Â 10 38 ergs s À1 in the 0.5-8 keV band, respectively, assum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 93 publications
(155 reference statements)
8
82
0
Order By: Relevance
“…This suggests that, if the nucleus of NGC 5195 is indeed currently active (as the molecular lines seem to suggest), it may be operating in the so-called radio-quiet or "high-excitation" mode characteristic of efficiently accreting massive black holes (Heckman & Best 2014), and consistent with the weak X-rays reported by Schlegel et al (2016). Alternatively, AGN signatures at optical and X-ray wavelengths previously reported by Moustakas et al (2010) and Terashima & Wilson (2004), respectively, may in fact be related to stellar processes or shocks occurring in the vicinity of the NGC 5195 nucleus (Lisenfeld & Völk 2010). If such a scenario in which the massive black hole in the center of NGC 5195 is in a quiescent state is indeed true, it is not clear what mechanism is responsible for halting AGN fueling given the abundant availability of cold gas.…”
Section: Radio-determined Star Formationsupporting
confidence: 64%
See 1 more Smart Citation
“…This suggests that, if the nucleus of NGC 5195 is indeed currently active (as the molecular lines seem to suggest), it may be operating in the so-called radio-quiet or "high-excitation" mode characteristic of efficiently accreting massive black holes (Heckman & Best 2014), and consistent with the weak X-rays reported by Schlegel et al (2016). Alternatively, AGN signatures at optical and X-ray wavelengths previously reported by Moustakas et al (2010) and Terashima & Wilson (2004), respectively, may in fact be related to stellar processes or shocks occurring in the vicinity of the NGC 5195 nucleus (Lisenfeld & Völk 2010). If such a scenario in which the massive black hole in the center of NGC 5195 is in a quiescent state is indeed true, it is not clear what mechanism is responsible for halting AGN fueling given the abundant availability of cold gas.…”
Section: Radio-determined Star Formationsupporting
confidence: 64%
“…Although Schweizer (1977) detected ionized gas emission lines in the galaxy, Ho et al (1997) and Moustakas et al (2010) found that the ionized gas line ratios are consistent with a low ionization nuclear emission line region (Kewley et al 2006). Weak X-ray emission was found coincident with a radio source, possibly due to an active galactic nucleus (AGN), but also consistent with an ultra-luminous X-ray source origin (Terashima & Wilson 2004;Schlegel et al 2016). Sage (1990) mapped NGC 5195 in 12 CO(1-0), and observed 12 CO(2-1) and 13 CO(1-0) with the National Radio Astronomy Observatory (NRAO) 12 m single dish, showing that there was molecular gas in the galaxy.…”
Section: Introductionmentioning
confidence: 97%
“…Terashima & Wilson (2004) studied Chandra data from 2000 and 2001 and found neither long term, nor shortterm variability in the full, soft, or hard energy bands. Since the Chandra observations from 2000 and 2001 were rejected from our sample because of the low number counts, we cannot compare our spectral fittings with theirs.…”
Section: Appendix B: Notes and Comparisons With Previous Results For mentioning
confidence: 99%
“…Lately, observational data indicating the possible existence of IMBHs have been accruing; some of the recent analyses are due to Portegies Zwart et al (2004), Roberts et al (2004), Terashima & Wilson (2004), and Cropper et al (2004), among others. A comprehensive review of the subject of IMBHs, including similar pieces of observational evidence, is presented in Miller & Colbert (2004).…”
Section: Introductionmentioning
confidence: 99%